Simulation and experimental analysis of biogas upgrading - Yonael Mezmur; Wondwossen Bogale (AIMS Energy, 2019)
Biogas production is a consolidated approach for converting organic waste into renewable energy. To better use the biogas and increase the calorific value and remove unwanted components from the raw biogas, it is crucial to clean raw biogas and upgrade it. The cleaned biogas is used in high efficient power generation systems. However, it is hard to find innovative biogas upgrading technologies for electricity generation in Ethiopia. Almost all of the Biogas produced in Ethiopia has been used for cooking. In this study, a novel technology to upgrade Biogas and reduce H2S content of biogas has been studied. After production of the biogas different chemicals have been used to upgrade the biogas: activated carbon to remove H2S, NaOH and KOH to remove CO2, silica gel and charcoal to remove the moisture. The experimental result shows that these innovative technologies reduces the acidic content (H2S) by 99% and removes the CO2content by 82%. As a result, the methane content increased from 56.7% to 85%. The CO2content decreased from 36% to 7%. This shows that the upgraded biogas can be used for electricity power generation.